Language and politics in Post-Soviet Russia : a corpus assisted approach - Koteyko, Nelya; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Language and Politics in Post-Soviet Russia critically examines the uses of language in post-Soviet media and political texts between 1998 and 2007. It will be of interest to academics and researchers in the fields of media studies, discourse analysis, corpus linguistics, and scholars in Russian Studies.
Keywords: History; Russia -- History; Europe, Eastern -- History; Political science; Linguistics; Applied linguistics; Sociolinguistics; Communication; Russian, Soviet, and East European History; Linguistics, general; Sociolinguistics; Applied Linguistics; Communication Studies; Political Science